RANCANG BANGUN TRAY DRYER SISTEM HYBRID (SURYA-HEATER) UNTUK PENGERINGAN IKAN ASIN - Yuliati, Selastia; Kalsum, Leila; Junaidi, Robert; HC, Fadarina; Azizah, Roro Rizqi Ramadhani; Utami, Winda Andea; Ningrum, Galuh Martiyah (KINETIKA, 2020)
Drying process on salted fish is one of the factors that determine the quality of the products produced. Conventional drying has many weaknesses, namely fluctuating heat, poor hygiene and requires a large enough space and can affect product quality. One of alternatives in drying salted fish is using a hybrid system tray dryer with a solar energy source with additional electrical energy (heater). This study aimed to design a tray dryer with hybrid system (solar-heater), obtained the performanced of the dryer based on drying rate, heat transfer and heat efficiency of the hybrid system tray dryer (solar-heater), and obtained salted fish that met the water content standards based on SNI No. 01-2721- 2009. The treatments varied were drying time of 60 minutes, 120 minutes, 180 minutes, 240 minutes and 300 minutes and the variations of drying temperature of 60oC, 70oC and 80oC. The results showed that the optimum drying conditions were drying using temperature of 70oC with a drying time of 300 minutes, a moisture content of 31.2%, a drying rate of 0.1492 kg/hour m2, a conduction heat transfer rate is 52.01 J, a convection heat transfer rate is 71.15 J, a radiation heat transfer rate is 0.048 J and heat efficiency of 53.28%.